Cordiosides A and B, two new 19-hydroxy-29-norlanostane glycosides isolated from the flowers of Cordia lutea. (December 2022) - Castro Dionicio, Inés Y.; Fabre, Nicolas; Saffon-Merceron, Nathalie; Sauvain, Michel; Castillo, Denis; Jullian, Valérie
Abstract: We present here the isolation and structural characterization of two undescribed mono-glycosylated triterpenes with a 19-hydroxy-29-norlanostane core. These compounds (1 -2 ) were isolated from an ethanolic extract of the dried flowers of Cordia lutea, a widely used Peruvian traditional medicine. Their structures were determined by examination of their NMR and MS data. For compound 1, its structure was confirmed by single crystal X-ray structural analyses. 1 showed moderate activity against Helicobacter pylori (MIC = 15.6 µg/mL), and was not active against Escherichia coli, Pseudomonas aeruginosa or Staphylococcus aureus (MIC > 125 µg/mL). Graphical Abstract: ga1 Highlights: Cordia lutea is a widely used as a medicinal plant in Peru. Little is known about its chemical composition. Two new 19-hydroxy-29-norlanostane triterpenes were isolated from this herbal remedy. One compound displayed moderate activity against Helicobacter pylori, supporting the traditional use of this plant.